Policy Conflicts and Inflation Targeting : The Role of Credit Markets - Choi, Woon (IMF Working Papers; Working Paper ;, 2018)
This paper shows that stabilizing volatility in credit growth often conflicts with price stability: unusual credit expansions often occur when inflation is low relative to goals, and credit slumps often appear when inflation is overshooting. We find that central banks with inflation targeting (IT) are responsive to credit conditions in both advanced economies and emerging-market economies (EMEs). However, EMEs are more sensitive to inflation conditions, responding to credit growth only when consistent with IT. Macroprudential measures are also deployed to address credit growth volatility when orthodox policy moves would be inconsistent with IT, complementing monetary policy.